اساسيات النظام البرلماني واشكالياتها في اقليم كوردستان-العراق دراسة تحليلية مقارنة - كريم, زانا رؤوف حمه; سعيد, دانا عبدالكريم (Journal of Legal and Political Studies, 2013)
The parliamentary system has achieved considerable success in practice in the United Kingdom after political and constitutional developments occurred over a long period of time in which the fundamental principles necessary for the establishment of this system has been finally shaped which is a two-tiered executive branch with flexible separation of power based on mutual checks and balances between the legislative and executive branches. Considering these advantages, many countries have adopted the parliamentary system including the Republic of Iraq according to the 2005 Constitution and the Kurdistan Region of Iraq under the applicable laws that have constitutional nature. However, the fundamental principles of this system have seen many shortages that created huge challenges to the nature of the parliamentary system in the Kurdistan Region making it ultimately a distorted parliamentary system. The major problem is that the legal and practical reality has eliminated the balance between the two branches because of the significance of the role of the President of the region and his exercise of actual powers which led to the forfeiture of many of fundamental principles of the parliamentary system. Thus, the mere existence of the system in Kurdistan has currently become dependent on the role the President plays in this system.
Keywords: parliamentary system; Separation of power; Constitution; checks and balances